2020
DOI: 10.1007/s00284-020-02167-0
|View full text |Cite
|
Sign up to set email alerts
|

Swabbing Thoroughly People for COVID-19 Positivity. Insights on the Main Bio-analytical and Microbiology Bias and Concerns

Abstract: Thorough swabbing is becoming an increasing approach to fight COVID-19 transmission, particularly among asymptomatic subjects, who are thought to represent the majority of potentially-contacting people. Particularly in the current management of COVID-19 emergency, the 3T approach, i.e., testing, tracing and treating, is felt as particularly crucial to fight COVID-19 pandemic. Aside from the time-consuming, cost expensive and the many burdensome issues associated with a thorough swabbing, adopting easy-to-make … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
1
0
2
Order By: Relevance
“…As already mentioned, the selection and the correct handling of samples for both molecular and serological analyses are fundamental for the diagnosis of COVID-19 infection. In particular, the collection of samples and the pre-analytical phases are crucial for the positive outcome of the diagnostic procedure ( 37 , 38 ). Different studies have demonstrated that the positivity rate of molecular tests significantly depends on the quality of the starting sample influenced by sample collection, poor quality material, wrong transport or storage, the presence of inhibitors, etc.…”
Section: The Right Test On the Right Sample At The Right Timementioning
confidence: 99%
“…As already mentioned, the selection and the correct handling of samples for both molecular and serological analyses are fundamental for the diagnosis of COVID-19 infection. In particular, the collection of samples and the pre-analytical phases are crucial for the positive outcome of the diagnostic procedure ( 37 , 38 ). Different studies have demonstrated that the positivity rate of molecular tests significantly depends on the quality of the starting sample influenced by sample collection, poor quality material, wrong transport or storage, the presence of inhibitors, etc.…”
Section: The Right Test On the Right Sample At The Right Timementioning
confidence: 99%
“…16 Penelitian Chirumbolo S tahun 2020 standar emas yang diakui saat ini adalah purifikasi RNA untuk kasus COVID-19. 17 Penelitian Mancini F et al tahun 2020 menjelaskan bahwa purification / pemurnian / purifikasi RNA standar emas untuk deteksi SARS-CoV-2. 18 Penelitian Boodman C et al tahun 2020 mendapati bahwa pengujian untuk SARSCoV-2 bergantung pada reaksi berantai polimerase transkripsi terbalik (RT-PCR).…”
Section: Bahasanunclassified
“…16 Penelitian Chirumbolo S tahun 2020 menjelaskan dari subjek asimtomatik, menunjukkan tingkat kegagalan yang jelas tinggi, karena banyak terkait bias dan kesalahan analitis. 17 Penelitian Habibzadeh P et al tahun 2020 mengingat sensitivitas rendah (tingkat negatif palsu yang tinggi) dari tes RT-PCR untuk diagnosis COVID-19 dalam sampel nasofaring. 20 Penelitian Caruana G et al tahun 2020 mendapati bahwa hasil negatif palsu dapat terjadi karena beberapa faktor seperti tidak adekuatnya sampel yang diambil melalui hidung, tingkat virulensi yang rendah, waktu pengambilan sampel, tipe spesimen (NP swab, OP swab, feses, sputum), dan transportasi (suhu, container).…”
Section: Bahasanunclassified